ANALISIS PRAKTIK JUAL BELI POHON CENGKEH DENGAN SYARAT HAK KEMBALI (BAI’AL-WAFA) DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Triani, Wanda; Akil, M; Lawang, Hasanna; Hasibuddin, M; Syahid, Akhmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze in-depth the practice of buying and selling clove trees with the condition of the right of return (bai' al-wafa) and assess its compliance with the principles of Islamic economic law in Dengeng-Dengeng Village, Pitu Riase District, Sidenreng Rappang Regency. The practice of bai' al-wafa is a form of transaction that has developed in society as a solution to urgent economic needs, but its implementation still raises debate among scholars because it has the potential to contain elements of gharar (uncertainty), usury, and injustice. Therefore, this study is important to conduct to provide an empirical description as well as a normative analysis of this practice. This study uses a qualitative method with a field research approach, which aims to understand the phenomenon contextually based on real conditions in society. Data collection techniques are carried out through direct observation of transaction practices, in-depth interviews with informants, and documentation as supporting data. The research subjects include clove farmers as sellers, buyers as fund providers, and religious leaders who have an understanding of Islamic law, especially muamalah fiqh. The data obtained were analyzed using a descriptive-analytical method, describing the facts that occurred in the field, then examining and interpreting them based on the concepts of muamalah jurisprudence and the provisions of Islamic economic law. This analysis focused on the clarity of the contract, fairness in the transaction, and the potential for elements prohibited by Islam. With this approach, the research is expected to provide a comprehensive understanding of the practice of bai' al-wafa and its implications for the application of Islamic economic principles in society.